Brief to the Sécrétariat à la jeunesse on the Politque Québécoise de la jeunesse, Axe IV : Active and Participatory Citizenship - Quebec Community Groups Network (QCGN) (2015)
This year the Quebec Community Groups Network (QCGN) is celebrating 20 years of leadership as a strong voice of the English-speaking Community of Quebec. The QCGN is a not-for-profit organization bringing together 49 English-language community organizations across Quebec. As a centre of evidence based expertise and collective action it identifies, explores and addresses strategic issues affecting the development and vitality of English-speaking Quebec and encourages dialogue and collaboration among its member organizations, individuals, community groups, institutions and leaders.

CLC Evaluation – The Quest for Sustainability & Best Practices : Final Report - Qu'anglo (2015)

CLC Evaluation – The Quest for Sustainability & Best Practices : Final Report : Executive Summary - Qu'anglo (2015)

Action Framework : Supporting the Well-Being of Minority English-Language Youth, Schools and Communities - Community Health and Social Services Network (CHSSN) (2015)

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Parallel title: School & Community Resources - Working Together is the Key!
Keywords: Official Language Minority Community (OLMC)